Synthesis of α-Hydroxyisovaleric acid (Hiv) and α-Acetyloxyisovaleric Acid (Ac-Hiv), Precursors of Aureobasidin B, with Improved Yield - Rani Maharani; Andi Rahim; Herdanu Rizqullah; Nur Muhammad Miftah; Ace Tatang Hidayat; Achmad Zainuddin; Nurlelasari Nurlelasari; Desi Harneti; Unang Supratman (Chimica et Natura Acta, 2018)
α-Hydroxyisovaleric acid (Ac-Hiv) and α-acetyloxyisovaleric acid (Ac-Hiv) have been successfully synthesized through a diazotisation of amino acid using sodium nitrite with the catalyst of sulfuric acid and acetic acid, respectively. In the synthesis of Hiv, Zubia et al. (2005) mentioned that 3 equivalents of sodium nitrite for the reaction gave the hydroxy acid with a good yield. However, Cohen-Arazi et al. (2008) described that 6 equivalents of sodium nitrite resulted the highest yield. In present study, a variation of equivalents of sodium nitrite (3, 4, 5, 6 eq.) were trialed for the same method of synthesis. Through several experiments, we found that 6 equivalents of sodium nitrite were the best portion among all. This finding was applied into the synthesis of protected Hiv (Ac-Hiv) that was previously reported by Maharani et al. (2017) giving 63% yield when 3 equivalent of sodium nitrite was employed. By increasing the equivalent of sodium nitrite into 6 equivalents, the Ac-Hiv can be synthesized with an improved yield (71%).